Specific detection of OCT4 isoforms in inflammatory bowel disease. Issue 1 (December 2015) - Maragkoudaki, Maria; Vaiopoulou, Anna; Theodoropoulos, George; Legaki, Evangelia; Sechi, Leonardo; Karamanolis, George; Zografos, George; Gazouli, Maria
Abstract Background Developmentally early cells are mobilized into peripheral blood in Crohn's disease (CD) patients. OCT4, is considered to be important in sustaining the pluripotency of stem cells.OCT4 splicing variants are differentially expressed in pluripotent and non-pluripotent cells. Our study aims to investigate the expression pattern of OCT4 variants and SOX-2, an essential factor implicated in self-renewal and pluripotency, in tissue and blood samples from patients with IBD. Methods Peripheral blood and tissue samples were collected from patients with active CD and ulcerative colitis (UC), and from healthy individuals. OCT4 expression was documented by Western blot, immunohistochemistry and by reverse transcription-real-time PCR.OCT4 isoform determination was documented using specific primers.SOX -2 expression levels were also evaluated. Results OCT4 protein levels were significantly higher in CD tissue samples than in CD blood samples, and in UC tissue samples. OCT4 protein was localized mainly in the cytosol. In all samples, only theOCT4 pseudogenes and theOCT4B1 variant were detected.OCT4B1 expression levels were elevated in both tissue and blood samples from CD and UC cases compared to healthy controls. In CD patients onlySOX -2 mRNA levels were found slightly increased compared to healthy controls. Conclusion Our results suggest that OCT4 is expressed in patients with IBD. Furthermore, we found the presence of theOCT4B1 isoform in IBD in both tissue and blood samples. Our results have shown, that developmentally early cells might be mobilized into peripheral blood as result of tissue damage, indicating a possible role of these cells in repair of injured intestinal tract.